An unusual presentation of cystic nephroma in an adult man - Lucio Dell'Atti (Rare Tumors, 2015)
Cystic nephroma (CN) is an uncommon, benign lesion of the kidney, whose clinical presentation is nonspecific with symptoms such as flack pain, hematuria and urinary tract infection. There are two peaks in the incidence of the tumor, with a bimodal distribution presenting in children between three months and two years, and in adults over 30-years of age. We report a case of CN in the middle part of the left kidney in a 66-year-old male that presented with a singular unilocular, well-circumscribed cyst containing numerous calcifications on the walls and with unremarkable thin or relatively thicker septa from the border with the renal parenchyma, but no solid components. Laparoscopic nephrectomy was performed. Images, histopathological and immunohistochemical features, that are potentially useful for refining this lesion, are discussed.